PROBLEM MINORITAS DALAM PERSPEKTIF AL-QUR’AN - Shomad, Bukhari Abdul (Universitas Islam Negeri Raden Intan Lampung, 2012)
Islam, more specifically, the Koran as its original source, has infrequently been made a scapegoat in a number of religious and ethnicity contained-humanitarian issues. This paper aims at tracing the Qur’anic paradigm of majority-minority relations in public life which is heterogeneous. By the use of humanistic hermeneutics, the author affirms the existence of Islam as a humanistic religion that upholds human rights and dictates the minority-majority relations set up in a frame of ummatan wasatan. The author analyzes the terms of human being in the language of the Koran, namely: al-insa>n, al- basyar and an-na>s which all shows the meaning of human equality in general, and furthermore, protection of their individuals and social rights in the frame of rahmatan lil ‘a>lami>n . According to the author, the term majority-minority is a new concern in Islam. In the context of community of religious diversity, Islam introduced the concept of “People of the Book” regardless of whether or not non-Muslim religious groups are in the position of minority or majority. The term Ahl azZ|immah used to refer to non-Muslim communities living under Islamic government can not also be equated with the term minority. The word “z” which means those under protection denotes their assurance of security and safety; hence this could not be interpreted as “helpless” or “inferiority”.